2018
DOI: 10.1142/s0218127418300057
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Motions in Forced Mixed Rayleigh–Liénard Oscillator with External and Parametric Periodic-Excitations

Abstract: This paper addresses the issue of a mixed Rayleigh–Liénard oscillator with external and parametric periodic-excitations. The Melnikov method is utilized to analytically determine the domain boundaries where horseshoe chaos appears. Routes to chaos are investigated through bifurcation structures, Lyapunov exponents, phase portraits and Poincaré sections. The effects of Rayleigh and Liénard parameters are analyzed. Results of analytical investigations are validated and complemented by numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…). Substituting equation ( 17) into (18) and evaluating the integral by using the standard integral tables [63], we obtain the Melnikov function:…”
Section: Fixed Points and Melnikov Criterion For Homoclinicmentioning
confidence: 99%
See 1 more Smart Citation
“…). Substituting equation ( 17) into (18) and evaluating the integral by using the standard integral tables [63], we obtain the Melnikov function:…”
Section: Fixed Points and Melnikov Criterion For Homoclinicmentioning
confidence: 99%
“…In recent years, the nonlinear dynamics of this class of oscillators has been intensively studied, and interesting results such as perioddoubling leading to chaotic motion, strange attractors, reverse period-doubling bifurcation, symmetry breaking, antimonotonicity, existence of horseshoe chaos, and so on have been obtained [17][18][19][20][21][22][23][24][25]. In most of these studies, the Melnikov perturbation method [18,24,26,27] has been widely used to detect chaotic dynamics and to analyze nearhomoclinic motion with deterministic or random perturbation. is method is today considered as a powerful analytical tool to provide an approximate criterion for the occurrence of hetero/homoclinic chaos in a wide class of dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…If M(τ 0 ) � 0 and dM/dτ 0 ≠ 0 for some τ 0 and some sets of parameters, then horseshoes exist, and chaos occurs [21][22][23][24][25]. Using this Melnikov criterion for the appearance of the intersection between the perturbed and unperturbed separatrixes, it is found that chaos appears when the following condition is satisfied:…”
Section: Horseshoe Chaosmentioning
confidence: 99%
“…e object of chaos theory is the study of nonlinear phenomena governed by simple and deterministic laws whose behavior under certain conditions becomes unpredictable. Since its discovery in the 20th century, chaos has been one of the most interesting for dynamic systems in areas such as physics, mathematics, chemistry, biochemistry, economics and finance, epidemiology, and engineering [19][20][21][22][23][24][25]. Depending on the field of study, it is sometimes useful or undesirable to the point where many researchers are interested in its prediction and/or control.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nonequilibrium phenomena such as oscillations, bistability, complex oscillations, and quasichaotic behavior of the reaction are revealed by these studies. One of the main challenges has been to predict and to control these phenomena in nonlinear chemical oscillations for potential applications (see [2][3][4][5][6][7][8][9][10][11][12][13][14][15]). e study of these oscillations has been made with a periodically external excitation or a parametric excitation [11,12].…”
Section: Introductionmentioning
confidence: 99%